Ambedkar : the attendant details - Yusufji, Salim
This book is an attempt at intimacy with B.R. Ambedkar in his hours away from history and headlines. The aim here is to recover the ephemera that attended Ambedkar’s life and died with him—his pleasure in his library and book-collecting, his vein of gruff humour, the sensation of seeing him in the flesh for the first time, or of stepping out of a summer storm into his house and hearing him at practice on his violin. Here, we have his attendants, admirers and companions speak of Ambedkar’s love of the sherwani, kurta, lungi, dhoti, and even his sudden paean to elasticated underpants. We meet Ambedkar the lover of dogs and outsize fountain pens, proponent of sex education and contraception, anti-prohibitionist teetotaler and occasional cook. The fragments that make up this volume enable the recovery of his many facets—a rewarding biographical quest.